2008
DOI: 10.2119/2007-00090.wen
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic Transformation of Human Small Airway Epithelial Cells Induced by Arsenic

Abstract: Human small airway epithelial cells (SAECs) previously immortalized with human telomerase reverse transcriptase (h-TERT) were continuously treated with sodium arsenite at a dose of 0.5 μg/mL in culture for up to 6 months. Arsenic-treated cells progressively displayed an increase in transformed phenotype including enhanced growth saturation density, plating efficiency, and anchorage-independent growth and invasion capability compared with their nontreated control cells. To determine whether arsenicinduced cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 44 publications
1
31
0
1
Order By: Relevance
“…In in vitro studies, neoplastic transformation caused by long-term exposure to low concentrations of inorganic arsenic was established in various cell lines (Achanzar et al, 2002;Sens et al, 2004;Wen et al, 2007;Li et al, 2010;Chain et al, 2004;Pi et al, 2008). For HBE cell line, Xu et al (2012) reported that HBE cells could be transformed by long-term (30 passages) exposure to 1.0 μM NaAsO 2 , as determined by anchorage-independent growth in soft agar and tumorigenesis in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro studies, neoplastic transformation caused by long-term exposure to low concentrations of inorganic arsenic was established in various cell lines (Achanzar et al, 2002;Sens et al, 2004;Wen et al, 2007;Li et al, 2010;Chain et al, 2004;Pi et al, 2008). For HBE cell line, Xu et al (2012) reported that HBE cells could be transformed by long-term (30 passages) exposure to 1.0 μM NaAsO 2 , as determined by anchorage-independent growth in soft agar and tumorigenesis in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure to arsenite causes carcinogenesis of lung, skin, and bladder (Shen et al 2008;Wen et al 2008). Long-term exposure to arsenite results in neoplastic transformation of human keratinocytes and small airway epithelial cells (Pi et al 2002;Wen et al 2008). The neoplastic transformation induced by low levels of arsenite is associated with cell proliferation (Wen et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to arsenite results in neoplastic transformation of human keratinocytes and small airway epithelial cells (Pi et al 2002;Wen et al 2008). The neoplastic transformation induced by low levels of arsenite is associated with cell proliferation (Wen et al 2008). In the present study, 0.5, 1.0, and 2.0 M concentrations of arsenite did not cause cell death and were lower than levels in drinking water in areas where arsenicosis is common (Pi et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations